Sustainable Agrochemistry A Compendium of Technologies - Vaz Jr., Sílvio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a broad range of technologies for sustainable agrochemistry, e.g. semiochemicals for pest management, nanotechnology for release of eco-friendly agrochemicals, and green chemistry principles for agriculture. It provides a concise introduction to sustainable agrochemistry for a professional audience, and highlights the main scientific and technological approaches that can be applied to modern agrochemistry. It also discusses various available technologies for reducing the negative impacts of agrochemicals on the environment and human health.
Introduction to Sustainable Agrochemistry -- Green Chemistry and Agriculture -- Semiochemicals for Integrated Pest Management -- Nanotechnology for Controlled Release and Formulation -- Fertilizers from Renewable Resources -- Spectroscopic Techniques for Crop Monitoring -- Humic Substances for Soils Improvement -- Synthesis of New Agrochemicals -- Toxicological Aspects of Agrochemicals -- Natural Pesticides for Crop Protection Chemistry -- Ecological Risk Assessment -- Management of Agrochemicals Residues in Water -- Glossary.
Keywords: Green chemistry; Refuse and refuse disposal; Agriculture; Soil science; Environmental monitoring; Green Chemistry; Waste Management/Waste Technology; Agriculture; Soil Science; Environmental Monitoring